Effect of Swirl Gas Injection on Bubble Characteristics in a Bubble Column - Ariny, Demong; Andrew Ragai, Henry Rigit; Khairuddin, Sanaullah (Semarak Ilmu Publishing, 2023)
Swirling gas injection is a well-known technique to improve mass transfer in bubble columns. It can be used to create small bubbles with a high surface area-to-volume ratio, which is beneficial for mass transfer. Swirl gas injection can also be used to create a more uniform bubble size distribution and improve the mixing of gas and liquid in the column. This study aims to determine the impact of swirl gas injection on bubble properties, including bubble shape, size, and velocity. A bubble detection approach has been developed for quick and precise determination of bubble size distributions in gas-liquid systems. Advanced digital image processing, including edge detection and bubble edge recognition, is used in this method. The experiment is conducted in a bubble column at a height of 57 cm and 61 cm. The column had a ring sparger and was made of Plexiglas. Tap water was used as the liquid, while air from an air compressor was utilized as the gas phase. The shape, size, population, and velocity of the bubble are measured using a high-speed digital camera. According to this study, the average bubble size reduced as the impeller speed increased, while the population of bubbles increased when the sparger rotation speed increased from 30 to 150 rpm.